2012
DOI: 10.5152/dir.2013.046
|View full text |Cite
|
Sign up to set email alerts
|

Tract-based spatial statistics of diffusion tensor imaging in hereditary spastic paraplegia with thin corpus callosum reveals widespread white matter changes

Abstract: NEURORADIOLOGYORIGINAL ARTICLE PURPOSE We aimed to investigate white matter diffusivity abnormalities in hereditary spastic paraplegia with thin corpus callosum (HSP-TCC) patients in relation with electrophysiological findings. MATERIALS AND METHODSBrain magnetic resonance imaging (MRI) and diffusion tensor imaging were performed on four HSP-TCC patients and 15 age-matched healthy subjects. Voxel-wise statistical analysis of fractional anisotropy, axial diffusivity, radial diffusivity, and mean diffusivity map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Average MD values were 1.07 and 0.89 × 10 -6 mm 2 /s in the genu and splenium of CC, respectively. [ 7 ] Reported values were similar to that in the present study, with the genu and anterior part of the body being most severely affected. Aghakhanyan et al .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Average MD values were 1.07 and 0.89 × 10 -6 mm 2 /s in the genu and splenium of CC, respectively. [ 7 ] Reported values were similar to that in the present study, with the genu and anterior part of the body being most severely affected. Aghakhanyan et al .…”
Section: Discussionsupporting
confidence: 89%
“…DTI often shows increased mean diffusivity and reduced fractional anisotropy in the CC and periventricular white matter, compatible with damaged myelinated axons. [ 7 ] Brain MRI and DTI performed on four HSP patients and 15 age-matched healthy subject by Oğuz et al . [ 7 ] reported that average FA values in genu and splenium were 0.55 and 0.72, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The common DTI indices are: fractional anisotropy, a measure of sensitivity to changes in orientation of axons along the tracts; mean diffusivity, a measure of magnitude of water diffusion and the presence of obstacles to diffusion [14,15], and radial diffusion, used to differentiate axonal injury from demyelination [13]. The most common radiological changes in a variety of HSP gene mutations are alterations in the corticospinal tract (70% of all studies, 71% of SPAST studies) and corpus callosum (80% of all studies, 86% of SPAST studies) [16,17,18,19,20,21,22,23,24,25]. Loss or damage to axons in the corticospinal tract are consistent with the motor symptoms of the disease, although white matter disturbances are not confined to the corticospinal tract and corpus callosum with involvement at the whole brain level, frontal and temporal lobes, cerebellum, and other regions.…”
Section: Radiology Of Hspmentioning
confidence: 99%